Evaluation of Anti-hyperlipidemic Activity of Red Onion In Experimental Animals - Kadam, Pooja; Chaware, Vitthal; Redasani, Vivek (Asian Journal of Pharmaceutical Research and Development, 2021)
Objective: To evaluate antihyperlipidemic effect of red onion on poloxamer 407 induced hyperlipidemia in wistar albino rats. Methods: Hyperlipidemia was induced by intraperitoneal injection of poloxamer-407 (P-407) at a dose of 1.0g/kg body weight in wistar albino rats. Drug treatments were done by oral gavage for 21 days. At the end of the study, animals were kept fasted over night and then blood samples were collected. The serum total cholesterol (TC), triglycerides (TG), and High density lipoprotein (HDL) were measured while low density lipoprotein (LDL) and very low density lipoprotein (VLDL) were calculated by Friedewald formula and atherogenic index was also calculated. Results: From the present investigation, it was observed that ethanolic extract of red onion have shown significant reduction in serum cholesterol, triglyceride and lipoprotein levels and increase in HDL level in P-407 induced hyperlipidemia. Conclusion: The findings in this study revealed the effectiveness of ethanolic extract of red onion against hyperlipidemic activity.